The Development of a care model for stroke patients admitted to inpatient wards with family participation at Pak Chom Hospital, Loei Province - Piakhwanon , Piyawan (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
This study aimed to develop a care model for stroke patients hospitalized in the inpatient ward through family participation at Pak Chom Hospital, Loei Province. It wasa participatory action research with purposive sampling. The sample consisted of 32 healthcare professionals working with stroke patients and 34 family members of stroke patients hospitalized in the inpatient ward. Data were analyzed using descriptive statistics, Paired t-test, and content analysis for qualitative data. Research findings revealed that after developing the patient care model: 1) Satisfaction among healthcare professionals and patient families was at the highest level, with mean scores of 4.26 and 4.47, respectively. 2) Family participation was high (Mean=4.51, SD=0.11), with the most prominent forms of participation being: decision-making about patient care (100%), direct patient care activities such as body cleaning, positioning, feeding, and physiotherapy (94.12%), and demonstrating correct and safe activity performance (91.18%). The research results indicate that the developed care model can effectively promote family participation in stroke patient care. Research recommendations suggest conducting further studies on knowledge of stroke patient care in inpatient wards and adherence to stroke patient care guidelines.